The Essence and Causes of Mass Panic: An Analysis of Data on the Beginning of Quarantine in Ukraine - Osadchenko, Inna I.; Perepeliuk, Tetiana D.; Baldyniuk, Olena D.; Masliuk, Ruslan V.; Semenov, Andrii A. (International Journal of Criminology and Sociology, 2021)
Based on the analysis of scientific information sources and empirical material (development and processing of the electronic questionnaire survey "Characteristics of mass behaviour in relation to COVID-19" in the social network "Facebook" at the beginning of the quarantine) clarified the nature of "mass panic" as a state of uncontrolled fear , panic state, confusion, a state of horror that increases when the real threat (COVID-19 pandemic) has become inevitably more threatening, and the imaginary danger of the consequences and further escalation of the pandemic acquires the magnitude of a real danger in person's consciousness, which blocks the ability to rationally evaluate the threat of disease and mobilize internal and external potential, self-control for individual/group/mass resistance to this danger. Four causes of the occurrence and intensity of mass panic are specified: individual and psychological, physiological, socio-situational, politically ideological conditions. Another dimension of mass panic, which the authors call "self-isolated individual-mass panic" is defined. It was stated that if people had the opportunity to gather on the street at the beginning of quarantine, there would be mass panic in its classic form. The panic developed at home, so people did not communicate physically, did not gather in crowds, interacted only by means of communication equipment. The mass mental state of Ukrainian citizens during the quarantine period can be considered a state of mass panic of various stages of intensity.